Comparable Rates of Gene Loss and Functional Divergence after Genome Duplications Early in Vertebrate Evolution - Nadeau, J. H. (1997)
Duplicated genes are an important source of new protein functions and novel developmental and physiological pathways. Whereas most models for fate of duplicated genes show that they tend to be rapidly lost, models for pathway evolution suggest that many duplicated genes rapidly acquire novel functions. Little empirical evidence is available, however, for the relative rates of gene loss vs. divergence to help resolve these contradictory expectations. Gene families resulting from genome duplications provide an opportunity to address this apparent contradiction. With genome duplication, the number of duplicated genes in a gene family is at most 2(n), where n is the number of duplications. The size of each gene family, e.g., 1, 2, 3, . . . , 2(n), reflects the patterns of gene loss vs. functional divergence after duplication. We focused on gene families in humans and mice that arose from genome duplications in early vertebrate evolution and we analyzed the frequency distribution of gene family size, i.e., the number of families with two, three or four members. All the models that we evaluated showed that duplicated genes are almost as likely to acquire a new and essential function as to be lost through acquisition of mutations that compromise protein function. An explanation for the unexpectedly high rate of functional divergence is that duplication allows genes to accumulate more neutral than disadvantageous mutations, thereby providing more opportunities to acquire diversified functions and pathways.